2020
DOI: 10.1111/ajt.15924
|View full text |Cite
|
Sign up to set email alerts
|

Early worsening of diabetic retinopathy after simultaneous pancreas and kidney transplantation—Myth or reality?

Abstract: Diabetic retinopathy (DR), a common long-term neurovascular complication of diabetes mellitus (DM) with a major impact on quality of life, is one of the leading causes of visual impairment worldwide. 1-3 Although the vascular component of its pathogenesis is undisputable, the importance of neurodegenerative and inflammatory processes in the retina has emerged only recently. 4 The functionality of the neurovascular unit and the integrity of the blood-retina barrier depend on the function and communication of ne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0
4

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 50 publications
(108 reference statements)
0
5
0
4
Order By: Relevance
“…Researchers do not dispute the importance of metabolic control in pancreatic transplant candidates, but they do not associate ocular changes after transplantation with differences in diabetes control before and after surgery. Normoglycaemia achieved as a result of surgery has a positive impact on the further course of previously diagnosed DR, which may result in its stabilization or improvement [133].…”
Section: Pancreatic Islet Transplantationmentioning
confidence: 99%
“…Researchers do not dispute the importance of metabolic control in pancreatic transplant candidates, but they do not associate ocular changes after transplantation with differences in diabetes control before and after surgery. Normoglycaemia achieved as a result of surgery has a positive impact on the further course of previously diagnosed DR, which may result in its stabilization or improvement [133].…”
Section: Pancreatic Islet Transplantationmentioning
confidence: 99%
“…A study looking at DR after combined kidney-pancreas transplantation showed early worsening (defined as 2.3 years following transplantation), characterized by vitreous hemorrhages and increased risk of cataract [183]. More recently, a sub-analysis of 43 patients from the ongoing randomized clinical study EMA-SPK, which will evaluate the differences in retinal neovascularization in patients with DR, has shown that 16 patients (37.2%) developed an early worsening of diabetic retinopathy within 12 months following a pancreas and kidney (PAK) transplant [184]. Several theories exist explaining why retinopathy may not remain stable following a pancreas transplant.…”
Section: Systemic Treatment Of Diabetic Retinopathy and Islet Cell Transplantationmentioning
confidence: 99%
“…El TP funcionante previene o reduce la nefropatía (41), mejora la polineuropatía periférica y autonómica (cardiaca, digestiva) (42) y mejora la enfermedad cardio-cerebro-vascular (43), aumenta el colesterol HDL y disminuye el colesterol LDL y la tensión arterial (44). Asimismo, la retinopatía se estabiliza o mejora a los 3 años del trasplante entre el 63% y 73% de los pacientes (45,46).…”
Section: Cuidados Perioperatorios Y Monitorización Del Injerto C0mplicaciones Pos-trasplanteunclassified